War and endogenous democracy - Davide Ticchi; Andrea Vindigni (Institute for the Study of Labor (IZA), 2008)
Many episodes of extension of franchise in the 19th and especially in the 20th century occurred during or in the aftermath of major wars. Motivated by this fact, we offer a theory of political transitions which focuses on the impact of international conflicts on domestic political institutions. We argue that mass-armies, which appeared in Europe after the French Revolution, are an effective military organization only if the conscripted citizens are willing to put effort in fighting wars, which in turn depends on the economic incentives that are provided to them. The need to provide such incentives implies that an oligarchy adopting a mass-army may voluntarily decide to promise some amount of income redistribution to its citizens, conditionally on satisfactory performance as soldiers. When the elite cannot credibly commit to provide an incentive-compatible redistribution, they may cope with the moral hazard problem of the citizens-soldiers only by relinquishing political power to them through the extension of franchise. This is because democracy always implements a highly redistributive fiscal policy, which makes fighting hard incentive-compatible for the citizens-soldiers. We show that a transition to democracy is more likely to occur when the external threat faced by an incumbent oligarchy is in some sense intermediate. A very high external threat allows the elite to make credible commitments of future income redistribution in favor of the citizens, while a limited external threat makes optimal for the elite not making any (economic or political) concession to the masses. Some historical evidence consistent with our theory is also provided.
urn:nbn:de:101:1-2008031813
Keywords: P16; 320; Autocracy; democracy; wars; redistribution; Politischer Wandel; Krieg; Kriegsfolgen; Demokratisierung; Verteilungspolitik; Autoritäres System; Public Choice; Theorie; Geschichte; Welt